Pasar Modal dan Karakteristik Investor Indonesia: Kasus Bursa Efek Jakarta - Chandra, Teddy (Jurnal Aplikasi Manajemen, 2009)
This article aims to describe the development of capital market in Indonesia-represented by Jakarta Stock Exchange (JSX) since the founding up to 2004 and to describe characteristics of investors in their tendency toward capital structure, corporate strategy, and the way they react on environment risks and how all of these bring effects on company's asset productivity, company's performance, and company's value as they sell their stocks in BEJ.